Using TMAI to determine the competitive position of companies in Poland’s chemical industry - Fura, Barbara Ewelina (Economic and Environmental Studies, 2019)
Currently, the fastest growth of the chemical industry is, besides the Asian markets, expected in the countries of Central and Eastern Europe, including Poland. However, the Polish chemical industry is facing several challenges such as high prices of raw materials, tougher environmental standards and growing competition from the rapidly growing Asian markets. It is, therefore, appropriate to define the competitive position of companies in the chemical industry in Poland. This goal was achieved through the use of the Taxonomic Measure of Attractiveness of Investment (TMAI), which belongs to a group of multidimensional comparative analysis. The assessment was made of 25 chemical companies listed on the Warsaw Stock Exchange (WSE) in Poland in terms of liquidity, debt, turnover, profitability and market efficiency. Companies were ranked in terms of their competitive position in two-time points, 2012 and 2016. Rankings were presented in two variants namely, with weighted and unweighted indicators. The research confirmed a compliance of companies’ rankings calculated in both variants of the applied method. Repeatedly high ranking positions were achieved by the majority of companies engaged in the production of mineral fertilizers. Although cosmetics companies were, in 2012, classified low, most of them recorded improvements in 2016. The opposite was observed in respect of manufacturers of pharmaceutical and medical products. The results obtained are useful in assessing the market value of companies in the chemical industry and in developing strategies for the development of the chemical industry in the light of sustainable development.